The Least Developed Countries Need to Strengthen and Broaden State Capacity to Operationalize Policy Space and Achieve Development Goals - United Nations Conference on Trade; Development (United Nations, 2022)
State capacity both drives improved development outcomes and is accumulated as a by-product of positive progression in the development process. However, the least developed countries have experienced attrition on both fronts. Development challenges among the least developed countries in the 2020s require them to develop and strengthen State capacity. These countries need the support of development partners through the implementation of programmes that intentionally reinforce and expand State capacity.